Framework of Sustainability Assessment (FSA) method for manufacturing industry in Malaysia - Nur Soliha, Sahimi; Faiz, Mohd Turan; Kartina, Johan (IOP Publishing, 2018)
In recent years, our planet faced massive social, environmental and economic challenges. Moreover, Environmental Democracy Index (EDI) published that Malaysia has been ranked as the second worst environmental democracy among 70 countries in May 2015. This is due to lack of participation in sustainability compliance and less awareness on sustainability by Malaysia's business partners. By combating and achieving these, the Sustainable Development Goals (SDGs) defines global priorities and inspirations through Agenda 2030 that recognize by United Nation. This paper attempts to propose Framework Sustainability Assessment (FSA) to assess sustainability for the various sector in Malaysia. This framework will give an overview to reduce the noise from wide data collection to a single element. Lastly, it will integrate the current performance with the linkage of the SDGs and the sustainability elements by dividing into three phase which is baselining, clustering and correlation. Now it is time for business to take action especially every sector or industry in Malaysia and it will improve the awareness and enhance Environmental Democracy Index to a better rank in future.